Using Hypnoteaching Strategy to Improve Students’ Speaking Ability - basir, achmad (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The use of hypnoteaching as a tool to improve students' speaking abilities is covered in this study. The purpose of this research is to determine how hypnoteaching can improve students' speaking skills. Using a pretest-posttest design for a single group, the writer employed a pre-experimental methodology in this research. Pre- and post-tests were distributed to the group. A pretest is used to gauge how well kids can speak. Following the completion of the pretest, the writer instructed the pupils in using the hypnoteaching technique. The final step involved administering a posttest to gauge the effectiveness of the treatment. The posttest results show how much the students' speaking skills have improved.Applying the hypnoteaching technique is a great way to assist students become more proficient speakers, as seen by the students' notable improvement in speaking after the treatment.